Pendidikan dan Pelatihan Filsafat dan Jatidiri Koperasi Bagi Aparatur Sipil Negara di Lingkungan Dinas Koperasi dan Usaha Kecil Provinsi Jawa Barat - Setiawati, Rosti (LPPM Universitas Koperasi Indonesia, 2024)
Cooperative Education and Training for State Civil Servants (ASN) within the West Java Province Cooperatives and Small Business Service with material on Cooperatives (Philosophy and Identity of Cooperatives) aimed at providing employees, especially State Civil Servants within the Cooperatives Service, who have an educational background. from various disciplines must have knowledge and understanding of cooperatives, so that in carrying out work it is always related to cooperative development. The output of this activity is that the 15 State Civil Servants who have just been accepted as employees in the West Java Province Cooperative and Small Business Service can understand about cooperatives, especially understanding the philosophy of cooperatives and the identity of cooperatives, and can also actively participate in cooperatives and in developing cooperatives. Cooperative education is very important for State Civil Servants so that they can increase their competence in carrying out their duties, so that development of small businesses and cooperatives can run effectively. So the State Civil Apparatus within the Department of Cooperatives and Small Businesses of West Java Province really needs an understanding of cooperatives, especially in terms of the philosophy and identity of cooperatives. Thus, the competency and skills of ASN within the West Java Province Cooperative Service are very necessary in developing and advancing cooperatives in West Java Province.